1970
DOI: 10.3329/jbcps.v28i1.4640
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Heart Failure Patients in a Tertiary Level Cardiac Hospital

Abstract: Objective: Heart failure (HF) has become an increasingly frequent cause of hospital admission and carries a poor prognosis. There is a paucity of data in Indo-Asians particularly in Bangladesh on characteristics of heart failure patients. The purpose of this study was to determine the etiological factors and co-morbidity of hospitalized heart failure patients. Method: A hospital based cross sectional study was done at a tertiary cardiac hospital in Dhaka city. Hospital medical records of 14009 patients admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…In DIG study (1997), 13 RALES study, 14 MERIT-HF study, 15 ATLAS Study 16 mean age was 64 years. M Kabiruzzaman et al 22 showed mean age was 54 years.…”
Section: Discussionmentioning
confidence: 99%
“…In DIG study (1997), 13 RALES study, 14 MERIT-HF study, 15 ATLAS Study 16 mean age was 64 years. M Kabiruzzaman et al 22 showed mean age was 54 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a hospital-based retrospective study at a tertiary cardiac hospital in Dhaka City 44 , about oneseventh (1970 out of 14009) of the patients admitted between January 2005 and August 2006 had heart failure. Majority (35.79%) had CAD as the principal etiological factor, whereas hypertension was the primary risk factor for HF in 29.14% of cases.…”
Section: Methodsmentioning
confidence: 99%
“…We also found that almost two thirds of the patients were male and one third were female, which is in coherence with most of the studies. [2][3][4][5][6][7][8][9][10][11][12] This may also attributed to the fact that less female patients come to hospital for treatment for various socio-economic factors. 14 In our study, the prevalence of cardiac emergency patient in DMCH was about 4.5% of the total emergency admission.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of our study population was 55.5 years, which is relatively lower than that observed in different studies done abroad. [2][3][4][5][6][7][8][9][10][11][12] According to the 2012 chartbook on cardiovascular, lung and blood diseases, heart disease was the leading cause of death for those aged 65 years and older 13 . The possible reasons for premature onset of Coronary Heart Disease in our country may be lack of awareness of morbid risk factors and appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation